2017
DOI: 10.1617/s11527-017-1027-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of hypercompacted earth for building construction

Abstract: This paper investigates the mechanical behaviour of a hypercompacted unstabilized earth material manufactured by compressing a moist soil to very high pressures up to 100 MPa. The hypercompaction procedure increases material density, which in turn improves mechanical characteristics. Samples were manufactured at the scale of both small cylinders and masonry bricks.The effect of ambient humidity on the mechanical characteristics of the material was investigated at the scale of cylindrical samples, showing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 20 publications
2
53
0
2
Order By: Relevance
“…Bruno et al [12] show that the grain size distribution and the plasticity properties of the material used in this work satisfy the requirements for raw earth construction [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bruno et al [12] show that the grain size distribution and the plasticity properties of the material used in this work satisfy the requirements for raw earth construction [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a small increase of dry density beyond the maximum value measured in this study could lead to a significant augmentation of compressive strength. Bruno et al [12] showed that the compressive strength of specimens compacted at a pressure of 100 MPa is already comparable with that of conventional masonry materials such as stabilised earth blocks and fired earth bricks.…”
Section: Figure 4 Variation Of Young Modulus With Dry Densitymentioning
confidence: 98%
See 1 more Smart Citation
“…It is also interesting to note that the maximum density obtained for each type of tested forming process was in the same range (between 2050 and 2080 kg/m 3 ). Using higher energy of compaction would result in a higher density as proposed by [34]. to 2100 kg/m3.…”
Section: Iii2 Effect Of Processing and Dispersantmentioning
confidence: 99%
“…Other authors have analysed the use of stabilized CEBs for affordable high-quality dwellings (Matta et al, 2015) or the addition of granitic soils to improve the mechanical properties of the units (Oliveira et al, 2016;Silva et al, 2015). Recent investigations on the behaviour of walls made using interlocking stabilized compressed earth blocks (ISCEBs) (Laursen et al, 2015;Qu et al, 2015 a,b) and the role of the compaction force (Bruno et al, 2017) have been carried out; in particular, the adoption of interlocking dry-stack blocks (Sturm et al, 2015) can simplify the execution phases. When this type of building exhibits box-type behaviour, the role of the out-of-plane behaviour must be evaluated in the seismic context (Qu et al, 2015 a,b;Andreini et al, 2013) or with regard to rocking phenomena in masonry walls (Giresini & Sassu, 2017;Giresini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%